Revealing the Role of Social Media and Creativity in the Success of MSME Culinary Business Performance - Pranawangrum, Indah; Ikut, Camilus Isidorus (Untag Business and Accounting Review, 2025)
This study aimed to determine the influence of social media and creativity on the business performance of culinary MSMEs. The population in this study consisted of all MSMEs in the culinary sector in Wonosalam District, Demak Regency, Central Java, Indonesia. The sample size used in this study was 80 respondents. The data analysis technique employed in this study was multiple linear regression analysis with classical assumptions. The results of the study demonstrated a positive effect of social media on business performance. Furthermore, the finding indicated that creativity had a positive influence on business performance. The conclusion stated that better social media and creativity led to better business performance.